ANALYTICAL DESCRIPTION OF ACIDS FOR CHEMICAL DIGESTION IN BIOLOGICAL SAMPLES EXPOSED TO METALS - Argota Pérez, George (2020)
The aim of the study was to describe the analytical concentration of acids for chemical digestion in biological samplesexposed to metals. Hydrochloric acid (HCl), nitric acid (HNO3), perchloric acid (HClO4), sulfuric acid (H2SO4), boric acid (H3BO3), phosphoric acid (H3PO4) and hydroiodic acid (HI) were analyzed. Experimentally the acids were applied to the gills of the Gambusia punctata biomonitor (Poey, 1854) for the bioextraction of cadmium metal. Th e certifi ed reference sample, DOLT-3 (Dogfi sh Liver), was used for the analytical reliability of the results. Statistically signifi cant diff erences were found in the results of acid concentrations and the certifi ed reference value. Th e order of concentration was: HNO3 > H2SO4 > HClO4 > HCl > HI > H3PO4 > H3BO3. It is concluded that acids allow to extract bioaccumulated metals in biological tissues, but their application, not combined with other acids, will diff er signifi cantly with the true bioaccumulated value. Th e highest odds for metal extraction are with HNO3, H2SO4 and HClO4.